Pengaruh Pola Asuh Orang Tua terhadap Hasil Belajar Siswa di MI At-Tablighiyah Ponjanan Timur - Astutik, Fitriyah Ika; Zainullah, Zainullah; Fajriyah, Fajriyah (Mitra PGMI: Jurnal Kependidikan MI, 2022)
This study aims to determine the effect of parenting on student learning outcomes at MI At-Tablighiyah Ponjanan Timur. The type of research used is quantitative research with a correlation research design. The variables involved in this study are parenting patterns and student learning outcomes. The subjects of this study were fourth grade students of MI At-Tablighiyah Ponjanan Timur, Batumarmar sub-district, Pamekasan Regency. This research was conducted in March 2021. The population in this study was 32 students. This research does not require a sample because the number of students does not reach 100 people. The data collection technique in this study used a test technique in the form of a questionnaire or a questionnaire sheet. The data analysis technique used in this study uses the Product Moment Correlation formula. Based on the analysis of the questionnaire data, it was obtained that rcount>rtable was 0.622 > 0.349 with a significance level of 5%, meaning that the hypothesis was accepted. So it can be concluded that there is an Influence of Parenting Patterns on Student Learning Outcomes at MI At-Tablighiyah Ponjanan Timur